Structural polymorphism of homopurine--homopyrimidine sequences: the secondary DNA structure adopted by a d(GA.CT)22 sequence in the presence of zinc ions. - Bernués, J (1989)
In this paper, we have analysed the conformational behaviour shown by the homopurine--homopyrimidine alternating d(GA.CT)22 sequence cloned into SV40. Our results show that, in the presence of zinc ions, the d(GA.CT)22 sequence adopts an altered secondary DNA structure (*H-DNA) which differs from either B-DNA or H-DNA. Formation of *H-DNA is facilitated by negative supercoiling and does not appear to require base protonation, since it is induced at neutral pH by approximately 0.4 mM ZnCl2. The patterns of OsO4 and DEPC modification obtained in the presence of zinc are compatible with a homopurine--homopurine--homopyridimine triplex, though other structural models for *H-DNA are also possible. The hypersensitivity to S1-cleavage of the d(GA.CT)22 sequence is reinterpreted in terms of the equilibria between the B-, H- and *H-forms of the sequence. These results reveal the high degree of structural polymorphism shown by homopurine-homopyrimidine sequences. Its biological relevance is discussed.